(untitled) (Educational Knowledge, 2023)
Throughout history, the teaching profession has borne the responsibility of nurturing virtues, potentials, and human qualities. Recognizing its transformative power, education has assigned both educational and societal functions to teachers, positioning them as agents of change capable of fostering the growth of human complexity. This article, a result of documentary review, reflects on teaching in the 21st century, elucidating challenges, dilemmas, and opportunities faced by educators in their daily practice. Moreover, it underscores the necessity of strategic actions that transcend content-centric approaches, prioritizing education for life and full engagement in global citizenship. The latter entails embracing diversity in sociocultural, ideological, and political contexts. The article concludes by emphasizing the teacher’s role redefinition, addressing emerging needs rooted in affective, spiritual, socio-emotional, and cognitive dimensions, vital for fostering well-rounded personality development.